HYPERTENSIVE OPTIC NEUROPATHY AS A PRESENTATION OF SYSTEMIC LUPUS ERYTHEMATOSUS - Zaini, Lia Meuthia; Mulya, Putri Nabillah (International Journal of Retina, 2025)
Introduction: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease affecting multiple organ systems, including the eyes. Hypertensive optic neuropathy is a rare but serious manifestation of SLE that may precede SLE diagnosis. This case highlights the early ocular involvement in a young patient with undiagnosed SLE. Case Report: A 21-year-old female presented to our ophthalmology clinic with blurry vision in both eyes, along with elevated blood pressure at 165/126 mmHg. Ophthalmic examination revealed visual acuity of 20/200 on both eyes, bilateral optic disc swelling, macular edema, flame-shaped hemorrhages, and cotton-wool spots. These findings are consistent with hypertensive optic neuropathy. The antihypertensive drugs were initiated and planned for intravitreal bevacizumab administration. The patient was referred to internal medicine. Laboratory tests and clinical findings indicated secondary hypertension, anemia, leukopenia, and thrombocytopenia. Immuno-serological testing confirmed a diagnosis of SLE. The patient was initiated on systemic immunosuppressive therapy. Eight weeks after the first visit, she showed significant improvement, with the resolution of macular edema and optic disc swelling. The patient’s visual acuity improved to 20/50 in the right eye (RE) and 20/20 in the left eye (LE). Discussion: Hypertension in SLE is multifactorial, involving endothelial dysfunction, kidney injury, immune activation, and autoantibodies. Hypertensive retinopathy progresses through three phases: vasoconstrictive, sclerotic, and exudative, characterized by arterial narrowing, structural vascular changes, and blood-retina barrier disruption, leading to macular edema and ischemia. Diagnosis is based on fundoscopic examination and Optical Coherence Tomography (OCT), while management focuses on blood pressure control, anti-VEGF therapy, and close monitoring to prevent further complications. Conclusion: Early detection and multidisciplinary management are crucial in preventing irreversible visual loss and systemic complications. Regular ophthalmic follow-up and blood pressure monitoring are essential in SLE management.